Cement catalyzed conversion of biomass into upgraded bio-oil through microwave metal interaction pyrolysis in aluminum coil reactor - Hussain, K. (Elsevier B.V., 2018)
Metal objects spark in the microwaves, exposing metals to melting point temperatures. The resulting heat can be utilized for the pyrolysis of biomass into upgraded bio oil. In this work pyrolysis was carried out both in the presence and absence of catalyst and the upgradation of bio oil was found the combine action of microwave heating, microwave effects and the catalytic activity of cement. Catalytic pyrolysis of biomass was carried out by mixing powdered biomass with fine powder of cement and placing the resulting mixture in an aluminum coil located in the baked clay reactor followed by its exposure to the microwaves. In this process aluminum coil was used as microwave receiving and heat generating antenna. All these experiments were carried out in a modified domestic microwave oven. The amount of product fractions like bio-oil, biogas and biochar was determined in terms of the mass of catalyst, time of reaction and the gauge of aluminum wire used for the preparation of coil. The bio oil obtained under the optimum conditions was analyzed using Gas chromatography mass spectrometry and the gaseous product was analyzed using chemical tests. Significant difference was observed in the chemical composition of bio oils prepared by catalytic and non-catalytic processes. Further, the oxygen contents of both types of the bio oil were found less than those to be obtained by conventional pyrolysis. Â© 2017 Elsevier B.V.